Influence of Gut–Liver Axis on Portal Hypertension in Advanced Chronic Liver Disease: The Gut Microbiome as a New Protagonist in Therapeutic Management - Francesco Santopaolo; Gaetano Coppola; Lucia Giuli; Antonio Gasbarrini; Francesca Romana Ponziani (Microbiology Research, 2022)
Clinically significant portal hypertension is associated with most complications of advanced chronic liver disease (ACLD), including variceal bleeding, ascites, spontaneous bacterial peritonitis, hepatorenal syndrome, and hepatic encephalopathy. Gut dysbiosis is a hallmark of ACLD with portal hypertension and consists of the overgrowth of potentially pathogenic bacteria and a decrease in autochthonous bacteria; additionally, congestion makes the intestinal barrier more permeable to bacteria and their products, which contributes to the development of complications through inflammatory mechanisms. This review summarizes current knowledge on the role of the gut–liver axis in the pathogenesis of portal hypertension, with a focus on therapies targeting portal hypertension and the gut microbiota. The modulation of the gut microbiota on several levels represents a major challenge in the upcoming years; in-depth characterization of the molecular and microbiological mechanisms linking the gut–liver axis to portal hypertension in a bidirectional relationship could pave the way to the identification of new therapeutic targets for innovative therapies in the management of ACLD.